Age-dependent increase of brain copper levels and expressions of copper regulatory proteins in the subventricular zone and choroid plexus - Fu, Sherleen; Jiang, Wendy; Zheng, Wei (Frontiers in Molecular Neuroscience, 2015)
Our recent data suggest a high accumulation of Cu in the subventricular zone (SVZ) along the wall of brain ventricles. Anatomically, SVZ is in direct contact with cerebrospinal fluid (CSF), which is secreted by a neighboring tissue choroid plexus. Changes in Cu regulatory gene expressions in the SVZ and choroid plexus as the function of aging may determine Cu levels in the CSF and SVZ. This study was designed to investigate associations between age, Cu levels, and Cu regulatory genes in SVZ and plexus. The SVZ and choroid plexus were dissected from brains of 3-week, 10-week or 9-month old male rats. Analyses by atomic absorption spectroscopy revealed that the SVZ of adult and old animals contained the highest Cu level compared with other tested brain regions. Significant positive correlations between age and Cu levels in SVZ and plexus were observed; the SVZ Cu level of old animals was 7.5- and 5.8-fold higher than those of young and adult rats (p<0.01), respectively. Quantitation by qPCR of the transcriptional expressions of Cu regulatory proteins showed that the SVZ expressed the highest level of Cu storage protein MTs, while the choroid plexus expressed the high level of Cu transporter protein Ctr1. Noticeably, Cu levels in the SVZ were positively associated with type B slow proliferating cell marker Gfap (p<0.05), but inversely associated with type A proliferating neuroblast marker Dcx (p<0.05) and type C transit amplifying progenitor marker Nestin (p<0.01). Dmt1 had significant positive correlations with age and Cu levels in the plexus (p<0.01). These findings suggest that Cu levels in all tested brain regions are increased as the function of age. The SVZ shows a different expression pattern of Cu-regulatory genes from the choroid plexus. The age-related increase of MTs and decrease of Ctr1 may contribute to the high Cu level in this neurogenesis active brain region.